Theoretical basis for quantitative evaluation of the expansion of the leading hole of a crushed stone bored pile in a nonlinear setting - A. Z. Ter-Martirosyan; Tran Manh Thiem (Vestnik MGSU)
Introduction. It is known that various methods are used to compact soft soils at depth, including the creation of soil columns by volumetric expansion of a portion of material (crushed stone, sand, etc.) under the influence of vertical load at the bottom of the well. With an increase in vertical load, the diameter of the working material increases to a certain value, resulting in significant radial and tangential stresses in the surrounding soft soil. This work is devoted to the development of the theoretical foundations for the manufacture of crushed stone bored piles that make it possible to quantify the stress-strain state in a soil cylinder due to the expansion of the diameter of the leading well. The formulation and solution of the problem of estimating the stress-strain state of a thick-walled soil cylinder of limited dimensions (diameter, height) with the diameter of a well are presented. Essentially, this is the well-known Lame problem of a thick-walled pipe.Materials and methods. The problem was considered in linear and nonlinear formulations. The solution was obtained by the analytical method. To estimate the stress-strain state of a thick-walled soil cylinder, the solution to the Lame problem of a thick-walled pipe and the system of Genki physical equations was used.Results. The expressions are obtained to determine the radial displacement of the borehole wall, radial and tangential stresses in the soil cylinder. The curves dependency of the radial displacement on radial pressure of borehole wall are shown. The achieved results are illustrated with graphics.Conclusions. The obtained solutions can be used to determine the radial displacement of the borehole wall during deep compaction of soft soils in linear and nonlinear formulations by adding crushed stone columns. The curves dependency of the radial displacement on radial pressure of borehole wall with various stiffness and strength parameters of the surrounding soils, as well as geometric parameters are presented.